2020
DOI: 10.1021/acs.jctc.9b01298
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Efficient Prediction of NMR Parameters of Condensed-Phase Systems with the Generalized Energy-Based Fragmentation Method

Abstract: We have implemented the calculations of NMR parameters within the generalized energy-based fragmentation (GEBF) method for condensed-phase systems with periodic boundary conditions (PBC). In this PBC-GEBF approach, NMR parameters of molecules in a unit cell are assembled as a linear combination of the corresponding quantities from a series of small embedded subsystems. To treat condensed-phase systems containing large molecules, we propose a novel “fragment-based” strategy for building subsystems, while our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 87 publications
5
44
0
Order By: Relevance
“…In Figure 4, we present a typical snapshot structure of this studied ILs as well as the structure of the [C 2 mim] + cation (with labeled H types). Our recent work demonstrated that for liquid water and a large macrocycle in solution, the ensemble‐averaged 1 H chemical shifts (over a few MD snapshots) obtained with the PBC‐GEBF approach at the B97‐2/pcSseg‐2 level are in good agreement with the experimental results 66 . Hence, to simulate the 1 H chemical shifts of [C 2 mim][BF 4 ] ILs, some snapshots of this ILs were also equidistantly selected along the MD trajectories.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In Figure 4, we present a typical snapshot structure of this studied ILs as well as the structure of the [C 2 mim] + cation (with labeled H types). Our recent work demonstrated that for liquid water and a large macrocycle in solution, the ensemble‐averaged 1 H chemical shifts (over a few MD snapshots) obtained with the PBC‐GEBF approach at the B97‐2/pcSseg‐2 level are in good agreement with the experimental results 66 . Hence, to simulate the 1 H chemical shifts of [C 2 mim][BF 4 ] ILs, some snapshots of this ILs were also equidistantly selected along the MD trajectories.…”
Section: Resultssupporting
confidence: 65%
“…b The experimental values are from ref 73. c Deviations of the PBC-GEBF calculated values relative to the corresponding experimental values. F I G U R E 4 Snapshot of the [C 2 mim] [BF 4 ] ILs (with 20 ion pairs, 480 atoms) and the [C 2 mim] + cation with the labeled H typessolution, the ensemble-averaged 1 H chemical shifts (over a few MD snapshots) obtained with the PBC-GEBF approach at the B97-2/ pcSseg-2 level are in good agreement with the experimental results 66. Hence, to simulate the 1 H chemical shifts of [C 2 mim][BF 4 ] ILs, some snapshots of this ILs were also equidistantly selected along the MD trajectories.…”
supporting
confidence: 75%
“…Due to the chemical complexities of proteins and the high computational costs of QM methods for large systems, building MLFFs for proteins remains a great challenge. Energy-based fragmentation (EBF) approaches [35][36][37][38][39][40][41][42][43][44][45] provide a practical and attractive solution to overcome these two difficulties. With this approach, the ground-state MLFF of a large system can be obtained as the linear combination of MLFF trained from small subsystems, which are representations of different local regions of a large system.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the chemical complexities of proteins and high computational costs of QM methods for large systems, building MLFFs for proteins remains a great challenge. Energy-based fragmentation (EBF) approaches [28][29][30][31][32][33][34][35][36][37][38] provide a practical and attractive solution to overcome these two difficulties. With this approach, the ground-state MLFF of a large system can be obtained as the linear combination of MLFF trained from small subsystems, which are representation of different local regions of a large system.…”
mentioning
confidence: 99%